2023
DOI: 10.15503/jecs2023.1.318.332
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Concerns in Higher Education: Impact of Covid-19 in Pedagogy

Abstract: Thesis. The present study aims to explore the impact of Covid-19 on higher education and identify the different problems faced by pedagogues around the globe. It compares the outcomes and comments from both established and developing countries to understand the change in pedagogical procedures. Concept. The desire for social isolation that was unheard of until the 20th and 21st centuries became a catchall word during the pandemic. For educational institutions, the governments’ emergency measures to switch from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The highlighted features suggested that Grammarly might be used effectively to assist ESL students at Darul Uloom Nadwatul Ulama in enhancing their writing abilities by reducing errors in the classroom and outside of it. Moreover, the studies [44][45][46][47][48][49] findings and results are in line with the present study which foregrounds the pedagogical issues of motivation amongst learners', use of online and blended module in language learning and its challenges, learners' issues, and especially writing issues of ESL learners [50][51][52][53][54].…”
Section: Discussionsupporting
confidence: 89%
“…The highlighted features suggested that Grammarly might be used effectively to assist ESL students at Darul Uloom Nadwatul Ulama in enhancing their writing abilities by reducing errors in the classroom and outside of it. Moreover, the studies [44][45][46][47][48][49] findings and results are in line with the present study which foregrounds the pedagogical issues of motivation amongst learners', use of online and blended module in language learning and its challenges, learners' issues, and especially writing issues of ESL learners [50][51][52][53][54].…”
Section: Discussionsupporting
confidence: 89%
“…The platform enables users to create profiles, share content, connect with friends and family, and engage in communities. With a user base numbering in the billions, Facebook has become a central platform for social interaction, information sharing, and online communication [54]. It has undergone advancements such as the addition of Facebook Messenger, Marketplace, and Groups, transforming it into a tool for both business endeavors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Roblyer et al, [19] demonstrated a significant difference in perception between university students and faculty members regarding the use of Facebook as a tool for classroom pedagogy. Some scholars argue that Web 2.0 technologies may not be suitable for formal ESL instruction [20], [21], [22], [23], [54]. Despite the reservations, it is essential to examine the pedagogical value of SNSs, especially in the context of teaching and learning of English as a second language.…”
mentioning
confidence: 99%
“…Such technologies in different educational settings can create the future generation of a workplace. Learning management systems present a viable opportunity for higher education institutions to reduce costs, particularly those that operate under tight financial constraints [8].…”
Section: A Web-based Instructionmentioning
confidence: 99%